JAMOL KAMOL SHE’RLARINING O’ZIGA XOS XUSUSIYATLARI - Nazarova, D. (SCIENCE and SOCIETY, 2019)
The works "Spiritual couplets" by Jaloliddin Rumiy and "The holy book" by Fariddin Attor in the translation of a talented translator Jamol Kamol take an honorable place on the shelves of libraries. The article is devoted to the analysis of enlightening ideas in the creation of the poet and his poetic skill.
Keywords: lyric hero; symbolic images; enlightening ideas; analysis; poetic skill